Defects and radiation-enhanced defect reactions in ZnSe/(001)GaAs MBE layers - Semenova, G.N.; Venger, E.F.; Korsunska, N.O.; Klad’ko, V.P.; Borkovska, L.V.; Semtsiv, M.P.; Sharibaev, M.B.; Kushnirenko, V.I.; Sadofyev, Yu.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Optical and structural properties of undoped ZnSe epilayers with thickness ranging from 0.5 to 2 mm grown by molecular beam epitaxy on GaAs (001) substrates have been investigated by depth resolved optical and X-ray methods. It was found that the epilayers with thicknesses above some value (>1 μm) contain three regions of different structural and optical quality. It is shown that two of these regions (near top surface and near interface ones) contain higher defect density. The nature of luminescence line at 446.1nm (4.2 K) is discussed. It was found that the radiation enhanced defect reactions occurred in the top surface region of epilayer.